EUROPEAN FUNDS AND REGIONAL GDP DYNAMICS IN ROMANIA. CASE STUDY: NORTH-WEST REGION AND BIHOR COUNTY - Marius-Florin MOȘ; Oana-Laura NICULA; Petru-Șandru ALBOI (Oradea Journal of Business and Economics)
This paper analyzes the relationship between the absorption of European funds, regional GDP dynamics, and the processes of local and regional development in Romania, with a focus on the North-West Region and Bihor County. Based on data provided by the National Institute of Statistics for the period 2000–2022, the study explores how investments made through the Cohesion Policy have influenced local economic and social development. Against the backdrop of a European framework that promotes territorial convergence, the research highlights that while European funds can be an important engine of development, their impact on GDP and local development varies significantly depending on the institutional, economic, and social context of each region or county. In Bihor’s case, a steady increase in GDP can be observed, along with persistent disparities when compared to counties such as Cluj, which has succeeded in building an innovation-driven economic model focused on high added-value services. The results show a positive correlation between attracted European funds and GDP growth, though not a directly proportional one. Thus, regional and local development cannot be assessed solely through GDP indicators, but must be examined in a broader framework that includes infrastructure, access to public services, social inclusion, administrative capacity, and quality of life. The paper argues that public policies should be grounded in an integrated approach, tailored to territorial needs, and that European funds must be aligned with clear objectives of sustainable, equitable, and balanced development.